Optical characteristics of p-type GaAs-based semiconductors towards applications in photoemission infrared detectors - Lao, Y. F. (2017)
Free-carrier effects in a p-type semiconductor including the intra-valence-band and inter-valence-band optical transitions are primarily responsible for its optical characteristics in infrared. Attention has been paid to the inter-valence-band transitions for the development of internal photoemission (IPE) mid-wave infrared (MWIR) photodetectors. The hole transition from the heavy-hole (HH) band to the spin-orbit split-off (SO) band has demonstrated potential applications for 3–5 μm detection without the need of cooling. However, the forbidden SO-HH transition at the Γ point (corresponding to a transition energy Δ0, which is the split-off gap between the HH and SO bands) creates a sharp drop around 3.6 μm in the spectral response of p-type GaAs/AlGaAs detectors. Here, we report a study on the optical characteristics of p-type GaAs-based semiconductors, including compressively strained InGaAs and GaAsSb, and a dilute magnetic semiconductor, GaMnAs. A model-independent fitting algorithm was used to derive the dielectric function from experimental reflection and transmission spectra. Results show that distinct absorption dip at Δ0 is observable in p-type InGaAs and GaAsSb, while GaMnAs displays enhanced absorption without degradation around Δ0. This implies the promise of using GaMnAs to develop MWIR IPE detectors. Discussions on the optical characteristics correlating with the valence-band structure and free-hole effects are presented.